2017
DOI: 10.1007/s00380-017-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of silent cerebral thromboembolic lesions after catheter ablation for atrial fibrillation in patients treated with direct oral anticoagulants

Abstract: There are few reports about the incidence and predictors of silent cerebral thromboembolic lesions (SCLs) after atrial fibrillation (AF) ablation in patients treated with direct oral anticoagulants (DOACs). The purpose of this study is to evaluate the incidence and predictors of SCLs after AF ablation with cerebral magnetic resonance imaging (C-MRI) in patients treated with DOACs. We enrolled 117 consecutive patients who underwent first AF ablation and received DOACs, including apixaban, dabigatran, edoxaban, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
2
13
2
Order By: Relevance
“…Intraprocedurally, the ACT management was suboptimal in a considerable number of patients, with ACT values less than 300 seconds. Univariate analysis identified a trend towards a higher likelihood for SCLs in patients with lower ACT values (<250 seconds), which is in accordance with previous observations . This again highlights the importance of proper anticoagulation management during the ablation procedure.…”
Section: Discussionsupporting
confidence: 89%
“…Intraprocedurally, the ACT management was suboptimal in a considerable number of patients, with ACT values less than 300 seconds. Univariate analysis identified a trend towards a higher likelihood for SCLs in patients with lower ACT values (<250 seconds), which is in accordance with previous observations . This again highlights the importance of proper anticoagulation management during the ablation procedure.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of SCEs in group C was 18.1% in the entire cohort and 10.0% in the matched‐pair group, respectively, and was similar to that reported in the previous studies with an RF‐based AF ablation guided by the CARTO system in the patients receiving periprocedural anticoagulation with uninterrupted warfarin and uninterrupted or minimally interrupted DOACs (0%–26.7%) 2‐4,8‐10 . On the other hand, the incidence of SCEs in Group R was 55.7% in the entire cohort and 51.7% in the matched‐pair group, respectively, and was much higher than that in Group C and those previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…Some predictors of SCEs after AF ablation have been reported, such as an older age, 7 nonparoxysmal AF, 5,11 higher CHA 2 DS 2 -VASc score, 9 reduced LA appendage flow velocity, 9 presence of spontaneous echo contrast, 7 lower ACT level, 5,9 extensive LA ablation, 7 and cardioversion during the procedure. 10 Nonparoxysmal AF was an independent positive predictor of SCEs in the present study, which was consistent with the results in the previous studies.…”
Section: Predictors Of Sces After Rf-based Af Ablationmentioning
confidence: 99%
“…It was 17.5% when warfarin was interrupted during the periprocedural period. Recently, Doi A et al found that CHA2DS2‐VASc score and minimal ACT during the procedure were independent predictors of ACE. These results indicate that thromboembolism is an important mechanism of ACE.…”
Section: Discussionmentioning
confidence: 99%